Customary tenure and innovative measures of safeguarding land rights in Africa: The community land initiative (iniciativa de terras comunitárias) in Mozambique - Ghebru, Hosaena H.; Pitoro, Raul; Woldeyohannes, Sileshi (International Food Policy Research Institute, 2015)
This research is conducted to contribute to the currently ongoing policy debate on the benefits of collective vis-à-vis individual land tenure rights. The paper attempts to explore the Mozambican community land delimitation (CLD) program based on a community-level survey conducted in mid-September 2014. The survey revealed that land conflict is the main reason to initiate a CLD process, and nongovernmental organizations (NGOs) are major players in initiating and helping the CLD process. Two-thirds of the CLD communities have completed all the necessary phases of the CLD process and received community land use certificates (Direito do Uso e Apreveitamento da Terra (DUAT). The major reason for not completing CLD processes is the withdrawal of the NGOs helping the process. More than 90 percent of the CLD communities mentioned improvement in land-related disputes both with other communities and within communities after the CLD process. Generally, not many significant differences are observed between the CLD and non-CLD communities. Land-related disputes are identified as the first most common dispute in 50 percent of the communities surveyed, with a difference between CLD (63 percent) and non-CLD (31 percent) communities. Similarly, land disputes are not only the first most common but also the first most difficult disputes in the surveyed communities. Among the surveyed communities were large-scale land acquisitions by domestic (35 percent) and foreign (10 percent) investors, with limited community involvement. The study found that CLD seems to have a strong demand from the non-CLD communities, as more than 50 percent of the non-CLD communities have a household-level willingness to pay for CLD process either in cash or in kind.